Let’s have fun with English: Exploring the Positive Impact of English Club on Peer Learning in an ELT Context - Akhmad, Zulkifli; Akhmad, Enni; Abas, Diki Setiawan (Journal of English Language Teaching, Linguistics, and Literature Studies, 2025)
In the English as a Foreign Language (EFL) context, formal classroom instruction often limits students’ opportunities to engage in authentic peer interaction and collaboration. Although English clubs are being used more frequently as extracurricular activities, not much study has been done on how they specifically support peer learning in casual settings. This study aims to examine the positive effects of English Club participation on peer learning among students in an EFL setting by identifying peer interaction types, collaborative learning strategies, and students' perceptions of their educational experience.  The researchers employed qualitative case study approach to collect data from 25 English education students at a state university in Gorontalo, Indonesia. For that purpose, semi-structured interviews, participant observation, and document analysis were implemented. The findings underpin Vygotsky’s sociocultural theory by emphasizing the social component of language learning. This study proposes a theoretical and practical contribution by highlighting the advantages of English Clubs a informal, student-centered environments that effectively uphold peer learning and communicative skills outside of the traditional classroom setting. The research result showed that English Club activities, such as group discussions, pair work, and peer tutoring, encouraged various forms of peer interaction. The collaborative behaviors such as peer correction, cooperative problem solving, and performance tasks are naturally developed in the Club. Students feel calmer and more confident to speak English, besides that their vocabulary and fluency improved. Keywords: English Club, peer learning, EFL context, Vygotsky’s sociocultural theory